2021
DOI: 10.1111/echo.15242
|View full text |Cite
|
Sign up to set email alerts
|

First trimester prenatal diagnosis of a severe tricuspid valve regurgitation and pulmonary valve atresia

Abstract: Early diagnosis of congenital heart defect (CHD) increased in the last two decades, following technological evolution. A recent meta‐analysis (Yu, 2020), on diagnostic accuracy in ultrasound detection of major CHD in the first trimester of pregnancy, reported an overall sensitivity of 75%. Ultrasound imaging of this case refers to a tricuspid valve dysplasia with right atriomegaly and pulmonary valve atresia diagnosed in a 13‐week gestational‐age fetus with low risk for chromosomal abnormalities. To our knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Fetal studies have implied that the outcomes after decompression of RV in infants with PA/IVS are associated with the degree of the TR ( 7 ). The absence or presence of mild baseline TR is a contributing factor to not reaching the desired BV circulation outcome ( 8 ). Lacobelli et al demonstrated that the absence of TR in fetal PA/IVS correlated to single ventricle circulation postnatally in addition to ventriculocoronary connections ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fetal studies have implied that the outcomes after decompression of RV in infants with PA/IVS are associated with the degree of the TR ( 7 ). The absence or presence of mild baseline TR is a contributing factor to not reaching the desired BV circulation outcome ( 8 ). Lacobelli et al demonstrated that the absence of TR in fetal PA/IVS correlated to single ventricle circulation postnatally in addition to ventriculocoronary connections ( 9 ).…”
Section: Discussionmentioning
confidence: 99%